AB0137 Effects and Mechanisms of Upar Expression in Rheumatoid Arthritis Fibroblast-Like Synoviocytes. (10th June 2014) - Yunfeng, P.; Yan, L.
Abstract : Background: uPAR is thought to promote the growth, metastasis and invasion of a variety of tumors. uPAR/uPA system is also found to be active in RA-FLS and associated with cell function. Thus, we suppose uPAR be closely related to disease progression of RA, but this kind of correlation is mediated by what mechanism, has not been reported. Objectives: To observe the effects and mechanisms of urokinase-type plasminogen activator receptor (uPAR) expression in rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS). Methods: Tissues were collected from RA patients with joint replacement surgery or arthroscopy and RA-FLS were obtained by tissue culture; Chemically synthesized small interference RNA (siRNA) specifically targeting uPAR gene was transfected into RA-FLS by cationic liposome; The interference efficiency of uPAR-siRNA on the production of uPAR mRNA and protein was determined by RT-qPCR and Western blotting respectly; The proliferative inhibition rate was examined by CCK8 assay; Flow cytometry was adopted to determine the change of cell cycle distribution; The migration of RA-FLS were examined by Transwell assay; Western blotting was performed to detect the influence of uPAR on PI3K/AKT signal pathway. Results: Transfection of uPAR-siRNA significantly decreased the mRNA and protein expression of uPAR gene; The proliferative inhibition rate was obviously higher in the uPAR-siRNA group than the control groups (P<0.05) after transfection for 48h (17.51±2.27)%, 72h (28.62±4.82)%, 96h (22.91±5.78)%. Flow cytometry assay showed accumulation of cells in the G0/G1 phase and the number of RA-FLS in the S and G2/M decreased; Transwell migration assay demonstrated the RA-FLS through the transwell membrane in uPAR-siRNA group (35±11) were lesser than the NC-siRNA group (136±19) <0.05) and the blank control group (138±21) (P<0.05). After transfected with uPAR-siRNA, the phosphorylation of PI3K/AKT/GSK3β decreased significantly. Conclusions: uPAR may play a role in the regulation of proliferation, cell cycle and migration of RA-FLS through activation of PI3K/AKT/GSK3β signal pathway. References: Serratì S, Margheri F, Chillà A, et al.Reduction of in vitro invasion and in vivo cartilage degradation in a SCID mouse model by loss of function of the fibrinolytic system of rheumatoid arthritis synovial fibroblasts [J]. Arthritis Rheum.2011, 63(9):2584-94. doi: 10.1002/art.30439. Malla R, Gopinath S, Alapati K, et al Downregulation of uPAR and cathepsin B induces apoptosis via regulation of Bcl-2 and Bax and inhibition of the PI3K/Akt pathway in gliomas. PLoS One.2010 Oct 29;5(10):e13731. doi:10. 1371/journal. pone. 0013731. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5304